2023
DOI: 10.21037/tp-22-418
|View full text |Cite
|
Sign up to set email alerts
|

Distal foundation augmentation enhances the “Bridge” role of single traditional growing rods in the treatment of severe early-onset scoliosis: a retrospective comparative cohort study

Abstract: Background: Dual traditional growing rod (dTGR) implantation may not always be feasible for patients with severe early-onset scoliosis (EOS). The concave single traditional growing rod (sTGR) can serve as a starting construct. Distal foundation augmentation (DFA) with four pedicle screws with a cross-link can increase the spinal control provided by a dTGR. However, DFA has yet to be used with a sTGR. This study investigated the efficiency of DFA in patients with severe EOS who underwent sTGR implantation.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that the use of single TGR as the only therapeutic modality is associated with important complications and should be avoided whenever an alternative is feasible [24]. However, Hai et al [25] reported similar outcomes using a single rod technique with distal foundation augmentation compared to classic dual rod technique.…”
Section: Treatmentmentioning
confidence: 99%
“…It has been reported that the use of single TGR as the only therapeutic modality is associated with important complications and should be avoided whenever an alternative is feasible [24]. However, Hai et al [25] reported similar outcomes using a single rod technique with distal foundation augmentation compared to classic dual rod technique.…”
Section: Treatmentmentioning
confidence: 99%